Dermoscopy of the iris: identification of Lisch nodules and contribution to the diagnosis of neurofibromatosis type 1 - Luciana Pavan Antoniolli; Laura de Mattos Milman; Renan Rangel Bonamigo (Sociedade Brasileira de Dermatologia, 2021)
Abstract Neurofibromatosis is a common genodermatosis, whose diagnosis often involves the participation of a dermatologist. A case of a 38-year-old female patient with four café-au-lait macules and eleven neurofibromas on clinical examination is presented. Dermoscopy allowed the identification of Lisch nodules in the iris, bilaterally. The combination of these findings allowed the diagnosis of neurofibromatosis type 1, according to NIH criteria. Lisch nodules are melanocytic hamartomas of the iris, which must be evaluated through a visual augmentation method, usually employed in ophthalmology. Alternatively, dermoscopy can be used and contribute to the early diagnosis of neurofibromatosis type 1.